Clinical feasibility and validation of the accelerated T2 mapping sequence GRAPPATINI in brain imaging. Issue 4 (April 2023) - Gruenebach, Natascha; Abello Mercado, Mario Alberto; Grauhan, Nils F.; Sanner, Antoine; Kronfeld, Andrea; Groppa, Sergiu; Schoeffling, Vanessa Ines; Hilbert, Tom; Brockmann, Marc A.; Othman, Ahmed E.
Abstract: Rationale and objectives: To prospectively evaluate feasibility and robustness of an accelerated T2 mapping sequence (GRAPPATINI) in brain imaging and to assess its synthetic T2-weighted images (sT2w) in comparison with a standard T2-weighted sequence (T2 TSE). Material and methods: Volunteers were included to evaluate the robustness and consecutive patients for morphological evaluation. They were scanned on a 3 T MR-scanner. Healthy volunteers underwent GRAPPATINI of the brain three times (day 1: scan/rescan; day 2: follow-up). Patients between the ages of 18 and 85 years who were able to provide written informed consent and who had no MRI contraindications were included. For morphological comparison two radiologists with 5 and 7 years of experience in brain MRI evaluated image quality using a Likert scale (1 being poor, 4 being excellent) in a blinded and randomized fashion. Results: Images were successfully acquired in ten volunteers with a mean age of 25 years (ranging from 22 to 31 years) and 52 patients (23 men/29 women) with a mean age of 55 years (range of 22–83 years). Most brain regions showed repeatable and reproducible T2 values (rescan: CoV 0.75%–2.06%, ICC 69%–92.3%; follow-up: CoV 0.41%–1.59%, ICC 79.4%–95.8%), except for the caudate nucleus (rescan: CoV 7.25%, ICC 66.3%; follow-up: CoV 4.78%, ICC 80.9%). Image quality of sT2w was rated inferior to T2 TSE (median for T2 TSE: 3; sT2w: 1–2), but measurements revealed good interrater reliability of sT2w (lesion counting: ICC 0.85; diameter measure: ICC 0.68 and 0.67). Conclusion: GRAPPATINI is a feasible and robust T2 mapping sequence of the brain on intra- and intersubject level. The resulting sT2w depict brain lesions comparable to T2 TSE despite its inferior image quality.